SOME ASPECTS OF MORBIDITY AND PREVENTION OF HDFN - Елена Николаевна Кравченко; Мария Александровна Ожерельева; Лариса Владимировна Куклина (The Publishing House Medicine and Enlightenment, 2017)
The purpose of the study was to investigate the incidence of hemolytic disease in the Rh-immunization of women and its prevention in the region of the Russian Federation for the 2010-2014. Material and methods. The data were analyzed annual reports of the health care budget of the Omsk region «City Clinical Perinatal Center» Omsk in the past five years. In parallel, we conducted monitoring research volume of preventive measures in the management and delivery of pregnant women with Rh-negative blood. Results. In the last five years, the total annual number of births increased by 41,2 %, 2,9 times increased incidence of hemolytic disease of children (HD). It was found that 36,1 % of newborns with hypertension require treatment in an intensive care unit and intensive care unit; 24 (20,8 %) is in need of exchange transfusion. Cases of early neonatal (1) and infant (1) mortality. According to the results of the survey revealed that the total volume of preventive measures (prophylaxis at 28 weeks of gestation and the postpartum period), made only 5 of the 235 (2,1 %) surveyed women with Rh-negative blood. Conclusion. The share of women with Rh-negative blood is on average 13,5 %, while the incidence of HD in the number of cases per 1000 births averaged 12,3 ‰, there was a significant increase in the number of newborns that require monitoring and treatment conditions. Increased incidence HD for the analyzed periods of time due to the insufficient preventive measures carried out in a planned manner and in the event of potentially sensitizing events.